SYSTEMATIC LITERATURE REVIEW: PENGARUH DISCOVERY LEARNING BERBANTUAN SCAFFOLDING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Fitrianny, Ashyifa Maulia Al; Rofiroh, Rofiroh; Nirmalasari, Dinar (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to examine the effectiveness of implementing a discovery learning model combined with scaffolding techniques in improving students' mathematical problem-solving competencies through a Systematic Literature Review approach. The underlying problem of this study is the low ability of students to solve mathematical problems due to the dominance of conventional learning approaches that are still teacher-centered. The Discovery Learning model provides opportunities for students to construct conceptual understanding independently, but in practice, students often require guidance. Therefore, scaffolding techniques are needed to direct the learning process to be more systematic and meaningful. This study analyzed 15 scientific articles with a publication period of 2020–2025 from Google Scholar, Publish or Perish, Sinta, and Garuda using the PRISMA-based Systematic Literature Review method. The analysis of these findings can be concluded that Discovery Learning assisted by scaffolding is proven to be effective in improving mathematical problem-solving abilities the use of this model is better than the use of conventional models. Scaffolding supports each stage of problem-solving, reduces cognitive load, and increases student motivation. The integration of Discovery Learning assisted by scaffolding, effectively develops students' mathematical problem-solving abilities